Developmental trajectories of soccer-specific dribbling and passing skills in young soccer players. - Gråsten, A.; Forsman, H.; Mainsbridge, C. (Journal of Physical Education Research, 2018)
The purpose of this study was to examine developmental trajectories of soccer-specific dribbling and passing skills including birth cohort, birth month, and sex differences in young soccer players. A total of 3108 (860 girls, 2248 boys) Finnish competitive soccer players were followed through six measurement phases from the age of 10 years continuing until turning 14. The present findings showed that dribbling and passing skills appeared to improve over time. Girls achieved similar dribbling and passing skill scores as boys at the baseline more than two years later. The relative age effect was evident, as younger players (born in Jul-Dec) achieved the same dribbling and passing scores as older players (Jan-Jun) at the baseline a half year later. An unexpected finding was that a difference between older and younger players existed in changes of dribbling, not in passing test scores. Current findings indicated that skill development in soccer is a slow process with a great variation between individuals. It would be beneficial to all players but especially to girls and younger players to practice a wide range of soccer-related skills outside organized events, as practicing a variety of soccer skills may help to learn other specific skills.